Política de educação básica da Nova República: o começo do caminho: 1985-1986 - Lopes, Ruth Gonçalves de Faria (1990)
This study aims at analyzing the proposal of formulation and implementation of basie education policy of the New Republic during the years of 1985 and 1986 . It intends to examine the government decisions in the field of basie education as 'far as political. social and economics aspects are concerned as well as whether such decisions have been effective to change the picture of deficiene ies present in the brasilian education system.